Crude oil assay database - Speight, James G.
Knovel's Crude Oil Assay Database is a unique, interactive compilation of key physical and chemical properties for over 200 crude oils commonly available on the world market. The data compiled in the database were sourced directly from seven crude producers and government agencies, and this data set includes over 2300 data records covering composition, key properties, kinematic viscosity, hydrocarbon composition, distillation, thermal properties and fuel indices. Within each table, registered users can compare multiple crudes against each other, and sort, filter, select, and export property values for further analysis. The database can also be used to compare and correlate different oil properties across multiple crudes. The data will also be useful both in understanding how oil properties affect oil behavior in the refinery, and in predicting one property from another. This data compilation consists of actual data from crude oil producers and government agencies. It was gathered under the direction of a subject matter expert who has deep experience with using and vetting data from the most authoritative and reliable sources in the field. Compilation of the data was verified against the sources in two separate validation stages. Final product testing at Knovel emphasizes data integrity to sources and consistency with data models and leverages the skill sets of our team resources. Automated programmatic validation processes were performed to compare source against final published data and ensure fidelity to source data. All data are cited back to the source to enable the user to easily check accuracy or get more information.